2020
DOI: 10.1016/j.heliyon.2020.e04080
|View full text |Cite
|
Sign up to set email alerts
|

Safe schools for teens: preventing sexual abuse of urban poor teens, proof-of-concept study - Improving teachers' and students’ knowledge, skills and attitudes

Abstract: Child sexual abuse (CSA) is a difficult form of abuse to detect, with the peak age of reports from 13 to 15 years old. The recent revision of the Philippine school curriculum provided an opportunity to incorporate an educational intervention for prevention of CSA. This study aimed to improve the teachers' and students' knowledge, skills and attitudes on disclosure, identification, and reporting of CSA. This research is a two-phase proof-of-concept crosssectional study of 237 teachers and 1,458 Grade 7 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
0
16
0
9
Order By: Relevance
“…One of the main ethical guarantees in the protection of children rights and all the sample, is the fact that the organizations hard strong criteria to avoid unethical behavior ( Ramabu, 2020 ; Madrid et al., 2020 ). In this line, efficiency in the organization, coordination, monitoring, implementation, and evaluation in other projects were needed to eligibility criteria to get funding for European Union Projects.…”
Section: Methodsmentioning
confidence: 99%
“…One of the main ethical guarantees in the protection of children rights and all the sample, is the fact that the organizations hard strong criteria to avoid unethical behavior ( Ramabu, 2020 ; Madrid et al., 2020 ). In this line, efficiency in the organization, coordination, monitoring, implementation, and evaluation in other projects were needed to eligibility criteria to get funding for European Union Projects.…”
Section: Methodsmentioning
confidence: 99%
“…School bullying has been defined as "a specific form of aggression, which is intentional, repeated, and involves a disparity of power between the victims and perpetrators" (Olweus, 1993a,b). In addition, some studies found that sexual violence (McMahon et al, 2019;Madrid et al, 2020) and cyberbullying (Livazović and Ham, 2019;Ige, 2020) were two emerging forms of adolescent violence in today's society. Bullying is an extremely damaging type of violence present in schools all over the world (Zych et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(Warraitch et al, 2020). Heightened reactivity to emotions paired with an immature emotional regulatory capacity and susceptibility to peer influence have all been cited as causing adolescent behavior problems (Madrid et al, 2020) . It seems that integrating emotion regulation skills training with educational components might bring about more effective prevention of sexual abuse In a study of college students, Walsh and colleagues found that those with poor emotional regulation, (meaning they have difficulty acknowledging and accepting emotional states), may also have difficulty recognizing feelings of discomfort, fear, or distress.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that integrating emotion regulation skills training with educational components might bring about more effective prevention of sexual abuse In a study of college students, Walsh and colleagues found that those with poor emotional regulation, (meaning they have difficulty acknowledging and accepting emotional states), may also have difficulty recognizing feelings of discomfort, fear, or distress. Because of this, it is likely that they miss out on an internal signal that there is a need to escape a risk situation (Madrid et al, 2020).…”
Section: Discussionmentioning
confidence: 99%